Repatriation of Slovenian Nationals During Mobility Lockdowns Due to the COVID-19 Pandemic - Vah Jevšnik, Mojca; Milharčič Hladnik, Mirjam (Two Homelands, 2022)
Repatriation due to the outbreak of the COVID-19 pandemic was the most extensive assisted return in Slovenia’s history. The article explores governmental responsiveness to the struggles and social risks experienced by Slovenian nationals stranded abroad during the global outbreak of COVID-19 from February to April 2020. It builds on a review of EU and national-level reports, a qualitative analysis of media sources, and expert interviews. The article highlights the lack of detailed systemic guidelines on transnational social protection in crisis situations and argues that the success in the repatriation of Slovenian nationals can be primarily attributed to the ad hoc measures set in place by highly motivated and inventive consular staff.